Implementasi Higiene Sanitasi pada RPH Kategori I sebagai Syarat Produksi Daging Sehat - M. Fitri; H. Nuraini; R. Priyanto; Y. C. Endrawati (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Abbatoirs have to produce meat that complied requisite of safety, healthy, wholeness and halal. Animalorigin product have to requisite basic safety product which implementated of hygine sanitation asproduction processed. The research aim was to evaluate implementation of hygine sanitation systemon 1st categrory abbatoir at Bogor Regency to complied safety and quality assurance of product.Observations on the implementation of hygienic sanitation were carried out using an evaluation matrixof the suitability of physical requirements with the criterion parameter assessment method based onthe Regulation of the Minister of Agriculture Number 13/2010. The best suitability value (NK) of 3 wasobtained on the environmental hygiene indicator and the absence of the use of chemicals, while theother sanitation hygiene indicators were worth 2 (less appropriate). The results of testing on meat forthe content of Salmonella sp. is negative and the Total Plate Count test is between 7.1 x 103 - 5.2 x 104cfu/g below the SNI threshold (1.0 x 106 cfu/g). The test for E. coli in meat was above the threshold ofsuspected contamination from the water used. Validation of hygiene sanitation practices was carried outby means of Colliform swabs on knives, palms hand and clothing of officers. Colliform swab test of theofficer’s palm hand, which is 5.4 x 102 cfu/g, shows a value above the allowable threshold. The results ofthe evaluation of the application of sanitation and hygiene in the abattoir are quite good but still needimprovement. Priority improvements are the equipment of cleaning facilities, water quality testing andimprovement of personal hygiene understanding.